Vulnerability of the Belt and Road Initiative to External Water Dependency. Issue 1 (September 2021) - Wang, L P; Li, Z H
Abstract: The Belt and Road Initiative (BRI) was proposed by China, aiming to promote multilateral cooperation with the world. However, existing studies has shown the external water dependency of the Initiative on the rest economies (Non-BRI), which may enhance the vulnerability of production activities in BRI. To understand the vulnerability of the BRI to water scarcity in Non-BRI, this study evaluates the impacts of water scarcity in Non-BRI on BRI, by using a multi-regional input-output model. Results show that among all BRI, China, South Korea, Russia and India were most vulnerable to water scarcity in Non-BRI, especially Spain, Sudan, the United States and Australia. Water scarcity to Agriculture sectors of Non-BRI exerted widespread influences on the BRI trade system. This study analyses the vulnerability of the BRI induced by water dependency on Non-BRI by identifying critical nations and sectors, and informs stokeholds of the BRI to pay attentions on the water scarcity of their upstream to mitigate the supply chain risk, and thus achieve sustainable development.